Methodology Forming the International Marketing Strategy of Fruit and Vegetable Products - Tuygunoy Ahmadjanovna, Mamadjanova (International Journal of Psychosocial Rehabilitation, 2020)
The article studies the issues of improving the methodology for the formation of an international marketing strategy for fruit and vegetable products. The author presents the stages of developing marketing strategies for fruit and vegetable enterprises and summarizes the results of empirical research. According to the author, the global market of fruit and vegetable products differs from other markets by their product and consumer diversity and their geographical, national, historical, and regional characteristics and should be marketed in their own specific methodologies. The Republic of Uzbekistan was selected as the research object, and two countries with the major share in the export of fruits and vegetables, Kazakhstan and Russia, were selected as exporting countries. Purpose: The article provides important scientific advice on the development of export strategies in accessing international markets. Design/Methodology/Approach: Theoretical and methodological research on the implementation of the perspective marketing strategy for fruit and vegetable production and sales in Uzbekistan was developed based on the results of the Balassa index study and developed a model of marketing strategy implementation based on the results of the article. Findings: As a practical result, the marketing strategy options for the development of fruit and vegetable exports, based on the RSA benchmark, have been developed in the development of international marketing strategies for the export of fruit and vegetable products. Originality/Value: As a novelty of the research, the "Commodity Market" matrix developed by I. I.Ansoff was used in the research of the fruit and vegetable products market.